Pengaruh Strategi Competitive Advantage dan Citra Merek terhadap Minat Beli Produk Oppo dikalangan Mahasiswa UBB - Kartini; Listawati; Iska Nadiatus Solihah; Indah Noviyanti (Program Studi Manajemen dan Magister Manajemen, Fakultas Ekonomika dan Bisnis, Universitas Katolik Widya Mandira, 2024)
Competitive advantage and brand image are very important for a company so that its products can attract buyers' interest. Consumers are increasingly critical when choosing a product, encouraging companies to improve product quality so they can compete and avoid customer dissatisfaction and can compete fairly in their market with other similar companies. The aim of this research is to determine the influence of the competitive advantage strategy and brand image of the Oppo smartphone company on student purchasing interest at Bangka Belitung University. The research method used is a qualitative descriptive method, using research, data collection, observation and interviews. From the research results obtained, competitive advantage strategies and brand image greatly influence the buying interest of students at Bangka Belitung University towards Oppo smartphones.